PEMBERDAYAAN MASYARAKAT DESA DI SEKITAR TAMAN NASIONAL GUNUNG MERAPI MELALUI MODEL DESA KONSERVASI - , Lukman Hery Prasetyo ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Model Desa Konservasi (MDK) is a model of conservation approache that provides opportunities to the community around conservation area to engage actively in the management of conservation areas. MDK introduced since 2006 because previous implementation of community development programs that developed since 1993 around the conservation area are less than the target. The program also gives an opportunity for the public to gain access to the rise of forest it is committed as a long term program to support forest conservation. MDK in Ngargomulyo village was formed in 2011. Through this program the pressure in TNGM is expected to be reduced significantly. The research question are how far the MDK program's effectiveness in reducing the pressure on the TNGM area and what factors influence it. To answer the authors conducted a study that has moreless similar, that question is to assess the MDK program's effectiveness in reducing the pressure on the TNGM area and the factors that influence it. This study used deductive qualitative method to explore necessary information in order to obtain an actual description of community empowerment by looking at the outcome of some aspects and factors that effect the condition. The results of this study found that the MDK program is effective to empower communities in helping meet their needs and maintain the sustainability of forest resources. MDK program effectiveness can be seen from the increasing of the income (10-15%), knowledge, skills, conservation awareness, involvement in the management, formation of the institution and also water availability, meanwhile conflict, intensity and how far people activity into the forest is decreasing. The Forest conditions in Ngargomulyo Village with the implementation of the MDK program show a positive change. Adequate resources, effective communication, implementing attitude of implementer, good coordination among stakeholders, as well as rate of leaders in the community are success factors of MDK implementation in Ngargomulyo Village.